If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4x = 9x + -20 Reorder the terms: 6 + 4x = -20 + 9x Solving 6 + 4x = -20 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 6 + 4x + -9x = -20 + 9x + -9x Combine like terms: 4x + -9x = -5x 6 + -5x = -20 + 9x + -9x Combine like terms: 9x + -9x = 0 6 + -5x = -20 + 0 6 + -5x = -20 Add '-6' to each side of the equation. 6 + -6 + -5x = -20 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = -20 + -6 -5x = -20 + -6 Combine like terms: -20 + -6 = -26 -5x = -26 Divide each side by '-5'. x = 5.2 Simplifying x = 5.2
| -5.5a=15.5 | | (7+z)(2z+3)=0 | | -4-7(1+6r)=325 | | (-4-3x)*-8= | | 124x^2-210=25x | | 12x-13=-6x+17 | | 5(x+4)-(2x-7)=0 | | 12x-13=.5x+17 | | 4(x-2)+10=42 | | 7(y-1)=3(y+.66) | | e^6x=3.8 | | 2/3(12x-21)=90 | | 5x-y=150 | | -32/-9=8/b | | 2/7x=36 | | X+15+2x+34=13 | | 2y+6=5(y+.6) | | (1/2)(x-8)=(-2/3)(6-9x) | | 2k=5k-9 | | (4n^2+1)+(5-n^2)= | | a+6+3a=5 | | -2a-a=39 | | -2(d+6)=0 | | 3a-4.5=4.8 | | m/8=5/12 | | X=x+22 | | 3x-57=-5x+15 | | 6/3/4= | | -6m^2+23m+4=0 | | 3s-6+2w=-2+w | | 3(3a-1)-2=-32 | | 3x-57=-5x+115 |